‘Help Anytime Anywhere’: An Android Application Providing Help and Safety - Narang, Ashima (International Journal of Psychosocial Rehabilitation, 2020)
— Now a days, smart phones have become an important part of our lives. Number of people using smart phones has increased dynamically. These days, numerous innovative applications are being created to provide various services over the mobile phones. Mobile applications can also be used as the safety hazard. Motivated by this, we have created an application which provides a complete package of safety using various other applications like GPS. Women safety is one of the major concerns these days. The proposed application is useful in such cases as well. A facility is provided by the application, in case of challenging situation, for sending current GPS location along with text alert messages. Using this application, users can also call nearby hospitals, police stations, fire stations, blood banks around their location in case of emergency. Apart from this, the proposed application also works as a guide in problematic situations.